2018
DOI: 10.1007/s10753-018-0830-7
|View full text |Cite
|
Sign up to set email alerts
|

Immunodeficiency in Patients with Acute Exacerbation of Chronic Obstructive Pulmonary Disease

Abstract: Chronic obstructive pulmonary disease (COPD), characterized by progressive airway inflammation and irreversible airflow limitation, leads to serious decline in life quality. The acute exacerbation of COPD (AECOPD) results in high healthcare costs as well as a significant mortality rate. The most common cause of acute exacerbation is infection. Immune deficiency, which induces dysfunction of anti-infection, plays an important role in the pathogenesis of acute exacerbation. As described in this review, the immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…Several studies have found 25,26 that the increased number of T cells in the lungs and airways of patients with COPD correlated with disease severity, and the proportion of T cells in sputum was significantly increased during AECOPD compared to that in the stable phase. 27,28 Serum sIL-2R expression is increased with T-cell activation. Our study showed that the AECOPD patients with adverse outcomes who still smoked had a significantly higher serum concentration of sIL-2R than those patients with good outcomes, suggesting that cigarette smoke may promote the occurrence and development of COPD by activating T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found 25,26 that the increased number of T cells in the lungs and airways of patients with COPD correlated with disease severity, and the proportion of T cells in sputum was significantly increased during AECOPD compared to that in the stable phase. 27,28 Serum sIL-2R expression is increased with T-cell activation. Our study showed that the AECOPD patients with adverse outcomes who still smoked had a significantly higher serum concentration of sIL-2R than those patients with good outcomes, suggesting that cigarette smoke may promote the occurrence and development of COPD by activating T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Increased severity and frequency of ECOPD could also be due to a relative immune dysfunction, as indicated by an increased number of functionally suppressive circulating cells and effector T-cell dysfunction [87]. Indeed, peripheral lymphocytes obtained from patients with ECOPD exhibit impaired responsiveness to bacterial antigens compared to those with stable COPD and healthy controls [88].…”
Section: Severe Exacerbations Of Copdmentioning
confidence: 99%
“…Chronic obstructive pulmonary disease (COPD), a chronic airway inflammation, is characterized by a progressive and irreversible decline in lung function, and recurrent episodes of respiratory infection. Suppressed innate and adaptive immune responses to the respiratory pathogen are strongly associated with the acute exacerbation of COPD (AECOPD) and disease pathogenesis (18)(19)(20). Hence, we hypothesize that the presence of TTV might be related to the progression of COPD, and the TTV load may indicate the immune status of COPD patients.…”
Section: Introductionmentioning
confidence: 99%